Answer:
Half the length of the base is 12 cm
Step-by-step explanation:
Assume that the length of the base of the triangle is b and that the height of the triangle is h
We are given that:
Area of triangle is half the base multiplied by the height of the triangle
This means that:
Area of triangle =
![(1)/(2)*base*height](https://img.qammunity.org/2020/formulas/mathematics/college/y014z76ab9u8jv7kqoz62o84bd5trk0wty.png)
Now, we are given that:
Height of triangle = h = 3 cm
Area of triangle = 36 cm²
Substitute with these values in the above equation and solve for half the length of the base
This is done as follows:
![Area = (1)/(2) *base*height\\\\36 = (1)/(2)*b*3\\\\(1)/(2)b = (36)/(3)=12](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nj5cx45upk3egzl4hpdapbu0396p5c0tr9.png)
From the above, we can conclude that:
Half the length of the base of this triangle is 12 cm
Hope this helps :)